Confectionery gels: Effects of low calorie sweeteners on the rheological properties and microstructure of fish gelatin. (June 2017) - Cai, Luyun; Feng, Jianhui; Regenstein, Joe; Lv, Yanfang; Li, Jianrong
Abstract: Low calorie sweeteners, such as xylitol and stevia, are being used for confectionery gels. Xylitol is digested using the human's glucose pathway and stevia is a natural low calorie sweetener. However, the microstructure and rheological properties of fish gelatin (FG) confectionery gels with these sweeteners has not been studied. Therefore, the effects of xylitol or stevia at 0, 1, 3, 5, 10 and 20% on the rheological properties and microstructure of FG (6.67% w/w) were studied. The addition of xylitol at low concentrations (i.e., 3–5%) increased the gel strength. However, the gel strength decreased upon further addition of xylitol, likely due to the xylitol preventing gel network formation. The gel strength decreased as stevia increased, which might be attributed to an antagonism that prevents fish gelatin from forming three dimensional network structures. Fourier transform infrared (FTIR) spectroscopy showed that the overall intensities of Amides A, B, I, II, III and the Fingerprint region increased with increasing concentrations of xylitol and stevia, suggesting decreased molecular order. Xylitol had more pronounced effects than stevia, which probably was related to its greater solubility and number of OH groups. Graphical abstract: Highlights: The addition of low calorie sweeteners affected the physicochemical and microstructural properties of the gelatin. The intensity and position of FTIR absorption peak increased as xylitol or stevia increased. The effects of xylitol and stevia on the gelation kinetics, and gel strength of fish-gelatin co-gel systems were investigated. The gel strength was related to the concentration of xylitol or stevia. Xylitol had more pronounced effect than stevia.